2017
DOI: 10.1177/1756283x17690990
|View full text |Cite
|
Sign up to set email alerts
|

Universal molecular screening does not effectively detect Lynch syndrome in clinical practice

Abstract: Background:Lynch syndrome (LS) due to an inherited damaging mutation in mismatch repair (MMR) genes comprises 3% of all incident colorectal cancer (CRC). Molecular testing using immunohistochemistry (IHC) for MMR proteins is a recommended screening tool to identify LS in incident CRC. This study assessed outcomes of population-based routine molecular screening for diagnosis of LS in a regional center.Methods:We conducted a prospective, consecutive case series study of universal IHC testing on cases of resected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Furthermore, a recent provider study, most of whom were non-gastroenterologists, revealed inconsistent LS identification and ad hoc testing practices with IHC ordered by a variety of providers 25 . Prior research demonstrated that even when institutional universal (all CRC cases) IHC testing was recommended, some might still not undergo testing 26 . Furthermore, if results were abnormal, genetic testing referral was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent provider study, most of whom were non-gastroenterologists, revealed inconsistent LS identification and ad hoc testing practices with IHC ordered by a variety of providers 25 . Prior research demonstrated that even when institutional universal (all CRC cases) IHC testing was recommended, some might still not undergo testing 26 . Furthermore, if results were abnormal, genetic testing referral was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal availability of genomic resources in these settings is a target for intervention. Decreased access to genetic specialists is a significant barrier to genetic testing and diagnosing LS 26 . Rural location was demonstrated as a barrier to genetics evaluation for hereditary breast cancer for multiple reasons including lack of awareness and distance of services 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As universal tumor testing has become more widespread in clinical practice, data are now emerging that highlight CA CANCER J CLIN 2018;68:217-231 VOLUME 68 _ NUMBER 3 _ MAY/JUNE 2018 the real-world challenges of capitalizing on its theoretical benefits, particularly with regard to appropriate referral for genetic counseling and testing after abnormal MMR IHC and/or MSI test results. 24,30,74,75 Data also demonstrate that somatic NGS panels have the ability to assess somatic mutational burden as a highly concordant surrogate for MSI/defective MMR (dMMR) status, suggesting that such somatic testing may be able to replace traditional MMR IHC and MSI testing, especially when universally implemented for ascertainment of other clinically relevant somatic mutations (eg, Kirsten rat sarcoma [RAS] proto-oncogene homolog, GTPase [KRAS]; neuroblastoma RAS protooncogene, GTPase [NRAS]; and B-Raf proto-oncogene, serine/threonine kinase [BRAF] mutation status in CRC). 76,77 Another potential pitfall that has emerged as universal MMR IHC/MSI tumor testing has become widespread is the molecular diversity of sporadic forms of MSI/dMMR CRCs and ECs.…”
Section: Variants) Including Some Rare Individuals With Pathogenic Gmentioning
confidence: 99%
“…In tumor-first GC models, genetic screening is first performed on a sample of tumor tissue, often as part of a pathology workflow, with GC offered based on the tumor results. A total of 26 publications from six countries that reviewed patient outcomes of tumor testing were identified ( Table 7 ) [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. In total, 23 publications [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ], including four abstracts [ 90 , ...…”
Section: Resultsmentioning
confidence: 99%